Influence of core and maltose surface modification of PEIs on their interaction with plasma proteins-Human serum albumin and lysozyme - Wrobel, Dominika; Marcinkowska, Monika; Janaszewska, Anna; Appelhans, Dietmar; Voit, Brigitte; Klajnert-Maculewicz, Barbara; Bryszewska, Maria; Štofik, Marcel; Herma, Regina; Duchnowicz, Piotr; Maly, Jan (Colloids and surfaces. B, Biointerfaces, 2017)
Regardless of the route of administration, some or all of a therapeutic agent will appear in the blood stream, where it can act on blood cells and other components of the plasma. Recently we have shown that poly(ethylene imines) (PEIs) which interact with plasma proteins are taken up into erythrocyte membranes. These observations led us to investigate the interactions between maltose functionalized hyperbranched PEIs (PEI-Mal) and plasma proteins. Two model proteins were chosen - human serum albumin (HSA) (albumins constitute ∼60% of all plasma proteins), and lysozyme. HSA is a negatively charged 66kDa protein at neutral pH, whereas lysozyme is a positively charged 14kDa protein. Fluorescence quenching and changes in the conformation of the amino acid tryptophan, diameter and zeta potential of proteins were investigated to evaluate the interaction of PEI-Mal with proteins. PEI-Mal interacts with both types of proteins. The strength of dendritic glycopolymer interactions was generally weak, especially with lysozyme. Greater changes were found with HSA, mainly triggered by hydrogen bonds and the electrostatic interaction properties of dendritic glycopolymers. Moreover, the structure and the size of PEI-Mal macromolecules affected these interactions; larger macromolecules with more sugar groups (95% maltose units) interacted more strongly with proteins than smaller ones with lower sugar modification (33% maltose units). Due to (i) the proven overall low toxicity of sugar-modified PEIs and, (ii) their ability to interact preferentially through hydrogen bonds with proteins of human plasma or possibly with other interesting protein targets, PEI-Mal is a good candidate for creating therapeutic nanoparticles in the fast developing field of nanomedicine.
Keywords: Blood; maltosa; polyethyleny; krevní proteiny; Fluorescence; Blood Proteins; sérový albumin; Protein structure; Maltose; muramidasa; fluorescence; Dendrimers; Muramidase; Polymers; dendrimery; Serum Albumin; Imines; Humans; Polyethylenes; iminy; Dendritic glycopolymer; polymery; Plasma; Fluorescence quenching; Proteins; lidé